LEGAL FRAMEWORK FOR E-SYARIAH AND I-SYARIAH IN JUDICIAL SERVICE DELIVERY IN MALAYSIA: ITS DEVELOPMENT AND CHALLENGES (UUM Journal of Legal Studies, 2024)
The electronic technology transformation within the Syariah Court management system in Malaysia has created a new dimension which is geared towards a more efficient, comprehensive, and allinclusive Syariah Court service delivery process. This research aims to analyse the challenges in developing this Syariah Court management system, namely the e-Syariah system implemented at the Federal level and the i-Syariah system which is applicable in Sarawak. An in-depth investigation was conducted on the modules developed in the e-Syariah and i-Syariah systems to obtain inclusive research information on the areas of concerned. A qualitative research method was employed to explore the progressive challenges in developing the e-Syariah and i-Syariah systems, and this was followed by a comparison of the systems applied by the Civil Courts and the contents of the system applied by the Syariah judiciary institutions in Malaysia. The findings revealed several challenges in developing the Syariah Court management system in Malaysia from the perspective of legal provisions, as well as information and communications technology (ICT). This matter has been viewed positively by the Department of Syariah Judiciary Sarawak (JKSS) and the Department of Syariah Judiciary Malaysia (JKSM), leading to the close cooperation with the Sarawak Information System Sdn. Bhd. (SAINS) in developing i-Syariah and e-Syariah to be applied in the Civil Courts. An upgrade of the e-Syariah system was carried out by the JKSM to respond to the challenges of digital technology applications in Malaysia, hence enabling the delivery of Syariah judiciary service that can be implemented successfully, systematically, and dynamically.